ICT for education, development, and social justice - Vrasidas, Charalambos; Zembylas, Michalinos; Glass, Gene V (Emerald Publishing Limited : Information Age Publishing, 2009)
This volume provides examples of current developments on the role of ICT for education, development, and social justice within an international context. Chapters draw on advanced contemporary thinking from scholars and practitioners in the field to present case studies of how ICT can be used to promote sustainable development and social justice. Social justice is understood in a wide sense as the pursuit of democracy, justice and development in the struggle against any form of oppression; it is within this context that ICT is explored as a tool for social change. The objectives of this book are: - To analyze the philosophical, historical, political, and cultural backgrounds and contexts that are constitutive of contemporary challenges and tensions in the role of ICT for education, development, and social justice around the world; - To appreciate the contextual and international dimensions of the tensions and challenges faced by educators around the world and contribute to ongoing efforts to sketch a vision for addressing their needs; - To explore ways in which ICT in education can promote social justice and contribute toward sustaining communities around the world.
"CARDET, Centre for the Advancement of Research & Development in Educational Technology"--Page facing title page.
Keywords: Telecommunication in education -- Social aspects -- Developing countries.; Information technology -- Social aspects -- Developing countries.; Digital divide -- Developing countries.; Social justice -- Developing countries.; Education -- Computers & Technology.; Social discrimination and social justice.; Educational equipment and technology, computer-aided learning (CAL); elektronické knihy; electronic books